Natural gas and Israel's energy future : near-term decisions from a strategic perspective - Popper, Steven W., 1953- (RAND, 2009)
This document assesses the opportunities and risks that the government of Israel faces in shifting to an energy mix increasingly dominated by domestic and imported natural gas. The analysis seeks to help the Israeli government choose robust strategies for exploiting the use of natural gas by minimizing the potential consequences of relying more heavily on natural gas. It does this by applying newly developed methods for strategic planning and decisionmaking under deep uncertainty for these assessments. The analysis also considers broader issues related to energy in Israel.